PENGARUH LIKUIDITAS, SOLVABILITAS, DAN AKTIVITAS TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010 - 2014 - Siallagan, Henny Anita; Ukhriyawati, Catur Fatchu (BENING, 2016)
This study aims to determine the effect of Liquidity, Solvency, Activities of financial performance on a cigarette company listed on the Indonesian stock exchange. This study uses a quantitative approach. Data collection techniques used in this research is the method of documentation that is by collecting and recording the financial statements.                Source data used are secondary data from financial statements tobacco companies listed on the Stock Exchange the period 2010- 2014 which can be obtained through the website www.idx.co.id. The sampling technique used was purposive sampling with the number of respondents 3 companies. Data analysis method used is multiple regression linear regression analysis with menggunakaan SPSS 20 for Windows.               The study states that (1) partially Liquidity significant effect on financial performance, (2) Solvency no significant effect on financial performance (3) Activities significant effect on financial performance, (4) simultaneous Liquidity, Solvency, Activities significant effect on performance non financial companies listed on the Indonesia Stock Exchange in 2010-2014.